Quantity and morphology of microplastics in the Tehran and Nowshahr MSW incinerators ashes - Behzad Valizadeh; Mohammad Ali Abdoli; Rouhalla Mahmoudkhani; Yousef Abdossalami Asl (Scientific Reports)
Abstract Despite the advantages of Municipal Solid Waste (MSW) incinerators, including reducing landfilling and producing energy, the production of ash is a serious concerns, beside the emission of polluting gases. In this study, the quantity and characteristics of microplastics in the ash of active incinerators in Iran were investigated. For this purpose, sampling was done for one year and the microplastics in the ash were observed and analyzed by sophisticated laboratory equipment. The samples were dried at 65 ºC and sieved using a sieve with a pore diameter of 1.0 mm. NaCl saturated solution was used for microplastic extraction in flotation process. The abundance and characteristics of microplastics in each sample were analyzed using microscope and stereomicroscope. The results showed that in all ash samples, there were microplastics of different sizes, and in total, 65.3% of them were less than 10 µm in size. The number of microplastics in the samples of Tehran and Nowshahr incinerators varied from 104 to 212 and 68 to 193 per 100 g of samples, respectively. Raman spectroscopy results showed that the origin of most microplastic particles is related to polyvinyl chloride (35%) and polypropylene (22%). Blue was the dominant color of microplastics (41% in Tehran samples and 40.5% in Nowshahr samples) and green was the least frequent color of microplastics (5.4% in Tehran samples and 6.4% in Nowshahr samples). Elemental analysis results by Scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) also showed high percentage of metals including iron, manganese, and calcium, along with carbon, sodium and chlorine on the surface of the microplastic samples. Considering the environmental health concerns of microplastics, it can be inferred that MSW incinerators cannot terminate the emerging pollutant, namely microplastics, and necessary consideration requires to reduce the volume of plastics in the waste and incorporating environmental friendly measures to prevent releasing these pollutants into the environment.